Effect of magnesium silicate hydrate (M-S-H) formation on the local atomic arrangements and mechanical properties of calcium silicate hydrate (C-S-H): In situ X-ray scattering study. (September 2022) - Kim, Gyeongryul; Im, Sumin; Jee, Hyeonseok; Suh, Heongwon; Cho, Seongmin; Kanematsu, Manabu; Morooka, Satoshi; Koyama, Taku; Nishio, Yuhei; Machida, Akihiko; Kim, Jihoon; Bae, Sungchul
Abstract: This study explored the effect of M-S-H formation on the local atomic arrangements and mechanical properties of C-S-H. The elastic moduli of the samples were calculated using shifted atomic distances ( r ) and d-spacings ( d ) acquired by applying an external load on the pastes during X-ray scattering experiments. The experimental results indicated that the crystal structure of C-S-H remained intact with MgCl2 addition. At the highest Mg/Si ratio (Ca/Si = 0.6, Mg/Si = 0.2), change in the dominant phase occurred from C-S-H to M-S-H because the low pH environment hindered the formation of C-S-H and facilitated the formation of M-S-H. The elastic modulus decreased with increasing Mg/Si ratio up to 0.1 owing to both C-S-H destabilization and low M-S-H content in the samples. Conversely, the elastic modulus increased in the paste synthesized with the highest Mg/Si ratio because considerable M-S-H had formed, which exhibited a higher elastic modulus than C-S-H.